Método multirresíduo para determinação de agrotóxicos em mamão empregando QuEChERS e UHPLC-MS/MS - Malonn, Maíra Casali (2022)
Papaya is the fourth most consumed fruit in Brazil and the third most exported fruit by the country. In search of better results in production and greater resistance to diseases and pests, pesticides have their widespread use in agriculture due to their effectiveness in pest control, but indiscriminate use can harm human health and the environment. This work aimed to establish a method for the multiresidue determination of pesticides in papaya using the QuEChERS method and analysis by ultra-high performance liquid chromatography coupled with tandem mass spectrometry (UHPLCMS/MS). The parameters that influence the extraction efficiency were studied and, after finding the best extraction conditions, the method was validated. The analysis by UHPLC-MS/MS allowed the determination of analytes with high selectivity and detectability. The original modified QuEChERS method employing the polymeric sorbent Strata SDB-L in the extract cleaning step was validated for 110 compounds and presented adequate values of accuracy, with recoveries between 70 and 120%, and precision, with RSD <20%. The method limits of quantification ranged from 5 to 10 µg kg-1 and detection limits from 1.5 to 3 µg kg-1 . The validated method was used for the determination of pesticides in commercial papaya samples, and 17 pesticides of different classes were found, including five pesticides not authorized for papaya. Considering the results obtained, the use of the proposed method proved to be fast and efficient for the multiresidue determination of pesticides in papaya in routine analysis.